2005
DOI: 10.1017/s0022112005004076
|View full text |Cite
|
Sign up to set email alerts
|

Vortex shedding from a hydrofoil at high Reynolds number

Abstract: High Reynolds number (Re) wall-bounded turbulent flows occur in many hydro- and aerodynamic applications. However, the limited amount of high-Re experimental data has hampered the development and validation of scaling laws and modelling techniques applicable to such flows. This paper presents measurements of the turbulent flow near the trailing edge of a two-dimensional lifting surface at chord-based Reynolds numbers, Re$_{C}$, typical of heavy-lift aircraft wings and full-scale ship propellers. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 44 publications
2
13
1
Order By: Relevance
“…The distinct forms of vortical cavitation possible to emerge in various engineering applications have been categorized by (Arndt 2002). The development, temporal evolution and collapse of either or a combination of the aforementioned forms of vortex cavitation has been extensively investigated by experimental means in reference to shear flows (O'Hern 1990), as well as two-phase separated flows in clearance passages (Boulon et al 1999), over hydrofoils (Coutier-Delgosha et al 2007;Bourgoyne et al 2005) and past bluff bodies, e.g. spheres (Brandner et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinct forms of vortical cavitation possible to emerge in various engineering applications have been categorized by (Arndt 2002). The development, temporal evolution and collapse of either or a combination of the aforementioned forms of vortex cavitation has been extensively investigated by experimental means in reference to shear flows (O'Hern 1990), as well as two-phase separated flows in clearance passages (Boulon et al 1999), over hydrofoils (Coutier-Delgosha et al 2007;Bourgoyne et al 2005) and past bluff bodies, e.g. spheres (Brandner et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…spheres (Brandner et al 2010). Periodic vorticalcavity shedding in the wake of a hydrofoil has been demonstrated to be enhanced by the vertical velocity fluctuations, which provide the perturbation necessary to trigger a Kelvin-Helmholtz instability responsible for the vortex rollup (Bourgoyne et al 2005). A method of specifying the distinct deformation mode of a stationary tip-vortex cavity has been proposed by Pennings et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…More explicit investigation into the low-frequency regime is required to substantiate the claim of impulse-like behavior. Analysis of hot wire data at varying streamwise locations closer to the trailing edge (similar to that of Bourgoyne 2005) and excitation of the ns-DBD with a single pulse at F + ≤ 0.15 will help to further characterize this regime.…”
Section: Future Workmentioning
confidence: 99%
“…Bourgoyne et al [6,7] experimentally investigated the dominant features of flows over a two-dimensional (2D) hydrofoil with an antisinging trailing edge at Reynolds numbers ranging from 10 6 to 5 × 10 7 . They concluded that turbulent fluctuations in the near wake are Reynoldsnumber dependent because of the varying strengths of the structured near-wake vortex shedding.…”
Section: Introductionmentioning
confidence: 99%